Strategi Satpol PP dalam Penegakan Peraturan Wali Kota Sukabumi Tahun 2014 tentang Pembatasan Operasional Tempat Hiburan Malam di Kota Sukabumi - Muhamad Arspira Pamungkas Fusga; Agus Rasyid Chandra Wijaya (Asosiasi Peneliti dan Pengajar Ilmu Hukum Indonesia, 2025)
This study aims to analyze the efforts made by the Sukabumi City Civil Service Police Unit (Satpol PP) in enforcing Mayor Regulation Number 05 of 2014 concerning restrictions on the operating hours of night entertainment venues. The regulation was implemented to maintain public order, reduce social disturbances, and ensure community comfort, particularly during nighttime hours in urban environments. Using a sociological legal approach with qualitative methods, data were collected through interviews with relevant stakeholders, field observations, and literature reviews. The findings reveal that Satpol PP has undertaken various enforcement efforts, including routine patrols to monitor venue compliance, educational outreach to business owners regarding regulations, and administrative sanctions such as written warnings and temporary closures for violators. Despite these initiatives, several challenges hinder the optimal enforcement of the regulation. These include limited human resources and operational infrastructure within Satpol PP, inconsistent public awareness of the regulation, and resistance from certain business actors who view the regulation as a barrier to economic activity and local tourism development. Moreover, coordination between relevant agencies, such as tourism and licensing departments, remains suboptimal. This study emphasizes the need for stronger inter-agency synergy, increased budget allocation, and ongoing public education to foster better compliance. It also suggests capacity-building programs for enforcement officers and the implementation of community-based monitoring systems to enhance transparency and support. In conclusion, although Satpol PP has shown commitment to implementing the regulation, the effectiveness of enforcement can be significantly improved through strategic resource optimization, cross-sector collaboration, and a participatory approach involving both authorities and the community.